What should I know before ordering a bone marrow aspiration/biopsy in patients with vitamin B12 deficiency?. (8th July 2013) - Randhawa, Jaskirat; Ondrejka, Sarah L; Setrakian, Sebouh; Taylor, Harris
Abstract : Vitamin B12 deficiency is a well recognised cause of macrocytic anaemia and bone marrow failure. Bone marrow aspiration/biopsy is infrequently indicated for the diagnosis in this setting. However, if a bone marrow aspiration/biopsy is performed, it is important to recognise that it may show dysplastic changes mimicking myelodysplastic syndrome (MDS) or acute leukaemia. We report a case of a 66-year-old non-vegetarian man presenting with generalised weakness for 1 month and misdiagnosed on bone marrow biopsy as MDS. However, laboratory investigations revealed severe deficiency of vitamin B12 . Four weeks after starting vitamin B12 replacement the patient's complete blood counts reverted to normal.